الاستثمار في التشريع الجزائري في إطار القانون 22-18 التحفيزات والعراقيل - عمـراوي نبيل - مجاهد عثمان (جامعة المسيلة, 2024)
The current Algerian investment legislation kept the Algerian Investment Promotion Agency established in 2001, and also enshrined the advantages included in the 2016 amendment and called them the term incentive systems, referring to previous applied texts until they are updated, amended or abolished. It appears that the new legislation for the year 2022 came in Under external and internal pressures, economic globalization imposes economic legal rules of a liberal international nature governed by market law, while the internal need for foreign investment, technology and revenues to strengthen the national economy and create job opportunities and wealth led Algeria to reduce restrictions and obstacles, so the digital platform for the investor was created to create economic vitality and transparency. It was larger and reduced bureaucracy, and was devoted to broader and closer incentive systems to attract foreign direct investment and improve the investment climate. However, Algeria was unable to escape from the interventionist and planned economic thought in its latest legislative amendment for the year 2022, and while waiting for data on the reality of investment for the coming years, it seems that achieving the desired goals needs to Deeper and broader economic thought.
Keywords: Keywords: investment; incentive system; investment obstacles; investment reality.